El artículo 256 del código orgánico general de procesos regula o restringe el derecho constitucional de la defensa - Aguirre Lara, Marco Antonio (2017)
The General Organic Code of Processes, when it refers to the appeal, states: "Art. 256.- Origin. The appeal proceedings proceed against judgments and interlocutory orders issued within the first instance and against the measures with respect to which the law expressly grants this remedy. It will be interposed orally in the respective audience. " (The emphasis is for transcendence purposes). While article 76 of the Constitution, which establishes the minimum guarantees of any process, in paragraph (m), of numeral 7, as a right of people to defense includes that of literal m) that says, "To appeal the ruling or resolution in all the procedures in which is decided on their rights". Now, because of the last part of article 256 of the COGEP, the judges are demanding as a requirement, for the appeal to proceed, that the party wishing to exercise the right of appeal must be present at the hearing where it is given The judgment, resolution or providence. This position is creating or demanding a precondition for the exercise of a constitutional right, which in itself does not withstand an analysis since the exercise of rights can not be conditioned, in this case the human right to defense; This is how it establishes in its different numerals the article 11 of the Constitution that establishes. "2.- All persons are equal and enjoy the same rights, duties and opportunities. 3. The rights and guarantees established in the Constitution and in international human rights instruments shall be of direct and immediate application by and before any public, administrative or judicial servant or servant, ex officio or at the request of a party. ... 4. No legal rule may restrict the content of rights or constitutional guarantees. ... 8.- The content of the rights will be developed progressively through standards, jurisprudence and public policies ... Any act or omission of a regressive nature that unreasonably diminishes, impairs or annuls the exercise of rights will be unconstitutional. (...) ". Of this there are two opposing positions on the constitutionality and legality of the final part of Article 256. Those who defend the legality of the rule maintain that it regulates the right to appeal. Those who maintain the unconstitutionality of the rule argue that a prerequisite for the exercise of the appeal is being sought, which restricts this right. As grounds for the unconstitutionality of the final part of article 256 of the COGEP, the existence of the right to the appeal to the appeal, established in article 258 of the COGEP, is made. Another ground is the content of article 79 of the COGEP, antepenultimate paragraph that maintains, "It will be resolved in a motivated way in the same audience. The people will be notified with the oral pronouncement of the decision. For the interposition of resources, the terms will be counted from the notification of the sentence or written self. " This content gives the possibility to appeal once the resolution or sentence has been notified in writing, which is contrary to Article 256 that "establishes" that only the appeal can be heard at the oral hearing.